Silver Nanoparticles Incorporated Chitosan Hydrogel as a Potential Dressing Material for Diabetic Wound Healing in Nursing Care - Zhao, Ying; Sun, Qinqin (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Nursing care of diabetic wounds remains a significant challenge due to a variety of reasons including low blood flow, impaired activity of inflammatory responses, and high oxidative stress in the diabetic wounds bed. Materials and Methods: In the current research, silver Nanoparticles (AgNPs) were loaded into a chitosan hydrogel system to produce a potential wound dressing for treating diabetic wounds. Various in vitro studies such as scanning electron microscopy assay, cell viability assay, and swelling assay were performed in order to characterize the dressing system. Wound healing potential of the developed wound dressing was investigated in a rat model of excisional wound. Results: In vitro study confirmed the biocompatibility of these hydrogels. In vivo study showed that wounds treated with AgNPs/chitosan hydrogel had higher wound closure and histological restoration compared with other groups. Degree of inflammation and formation of epithelium in AgNPs-loaded hydrogels were improved compared with other groups. Conclusion: Our developed systems have potential applicability to be used as wound dressing in nursing care.
Keywords: Wound nursing care; Silver nanoparticles; Chitosan hydrogel; Drug delivery; Wound; dressing